PENGEMBANGAN MEDIA VIDEO ANIMASI BERBASIS APLIKASI CANVA PADA MATERI SISTEM ORGANISASI KEHIDUPAN - Ningsih, Widya; Yeni, Laili Fitri; Mardiyyaningsih, Asriah Nurdini (Universitas Tanjungpura, 2024)
This research aims to develop Canva based video animation as learning media for system organization of life. This media is intended to explain abstract concept of organization of life, specifically for explicating the concept of cells and tissues that cannot be observed without supporting tools, such as microscope. Moreover, the general content of life organization system is a complex material which discusses the comprehensive connection between the smallest to the largest unit of life. The research approach used 3 steps of 4D Thiagarajan development model: Define, Design, and Development. The media is then tested for its validity and reliability. The content validation of five experts was assessed by using Likert Scaled validation instrument. The instrument had been validated by two experts before applied. Validation of media includes 4 aspects: format, content, language, and usability of media. The validaton is determined using the Aiken's V formula. The reliability among validators is measured using ICC reliability test. The results shows the media which has been developed, validated and revised based on the validatiors